16. PREVELANCE OF MYOPIA AND RELATED FACTOR TO MYOPIA AMONG JUNIOR HIGH SCHOOL STUDENTS (Vietnam Journal of Community Medicine, 2025)
Background: Myopia is a common refractive error leading cause of distance vision impairment globally, especially among students.Objectives: To identify the prevalence of myopia and the factors related to myopia among junior high school students at Tuy An District, Phu Yen Province in 2024.Methos: A cross-sectional survey was conducted among 463 students at An Ninh Tay junior high school, Tuy An District, Phu Yen Province from March 27th, 2024 to May 1st, 2024. Subjects were surveyed using a prepared questionnaire and Myopia was assessed by the information supplied by the school health.Results: The prevalence of myopia in students was 8,9%. The students who are girls, have good learning outcomes, a family with history of myopia, frequency of taking extra classes, time spent on learning and wrong sitting posture, could easily have myopia than others.Conclusions: The prevalance of myopia is high among junior school students. The remedies should be taken to consciously protect their eyes including reducing time spent on learning, increasing time spent on exercises or outdoor activities and declincing behaviors and habits that harm the eyes.
Keywords: myopia; refrective error; junior students; Phu Yen